Transverse strength of railway tracks: part 2. Test system for ballast resistance in line measurement (Fracture and Structural Integrity, 2014)
In the present paper, testing methods currently adopted to measure the in service ballast resistanceare synthetically reviewed to identify the main sources of uncertainty influencing the test loads and to define anexperimental methodology allowing the optimal control of the testing parameters without the introduction ofspurious or parasitic actions on the track sample. An alternative testing system, which allows applying on a fullscalesample of a railway track testing loads very close the real ones, is presented. Of the new system, both theways of use for measuring the transversal and axial ballast strength, the general procedure to carry out theexperimentation and its application to a real scenario are described, highlighting its main advantages in termsboth of modalities for applying the loads and of testing parameter control.
Keywords: Test system